Differences in the treatment and control of hypertension in urban and rural residents of the northeastern region of the People's Republic of China: a cross-sectional study. (19th May 2019) - Zhao, Lei; Sun, Wei; Wang, Junnan; Wu, Junduo; Zhang, Yangyu; Liu, Yingyu; Liu, Bin
ABSTRACT: Background : Hypertension is a significant global public health problem and an important risk factor for cardiovascular diseases. We aimed to determine treatment and control rates of hypertension and to explore related risk factors by urban and rural areas. Methods : A cross-sectional survey of 14, 956 participants (≥ 15 years) was conducted in Jilin Province, China from July 2014 to December 2015 using questionnaire forms and physical measurements. Results : Total rates of hypertension treatment, control, and controlled blood pressure among treated subjects were 31.7%, 8.8%, and 27.9% in the Jilin Province. Rates of hypertension treatment, control, and controlled blood pressure among treated subjects were 35.9%, 13.7%, and 38.3% in urban areas and 28.4%, 5.0%, and 17.5% in rural areas, respectively. Higher treatment of hypertension was associated with older age, female sex, other races (except Han), and higher body fat percentage in both areas. Among urban residents, higher education was additionally associated with higher treatment of hypertension; among rural residents, a family history of coronary artery disease and unemployment were associated with higher treatment of hypertension. Higher control of hypertension was associated with unemployment, married status, higher education, healthy body mass index, lower abdominal waist circumference, non-smoking status, and lower visceral adiposity index in urban residents; higher control of hypertension was associated with younger age in rural residents. Conclusion : Treatment and control rates of hypertension in urban and rural areas were lower than the national average; blood pressure control in patients taking antihypertensive drugs needs further improvement.